2009
DOI: 10.1074/jbc.m109.016865
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Src Homology 2 Domain-containing Inositol 5′-Phosphatase (SHIP1) by the Cyclic AMP-dependent Protein Kinase

Abstract: Many agents that activate hematopoietic cells use phosphatidylinositol 3,4,5-trisphosphate (PtdIns 3,4,5-P 3 ) to initiate signaling cascades. The SH2 domain-containing inositol 5 phosphatase, SHIP1, regulates hematopoietic cell function by opposing the action of phosphatidylinositol 3-kinase and reducing the levels of PtdIns 3,4,5-P 3 . Activation of the cyclic AMPdependent protein kinase (PKA) also opposes many of the proinflammatory responses of hematopoietic cells. We tested to see whether the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…However, it is not clear that this phosphorylation event can regulate SHIP1 activity (14). We have demonstrated that SHIP1 can be phosphorylated and activated by the cyclic AMPdependent protein kinase (PKA) both in vitro and in cells, highlighting a new mode of SHIP1 regulation (18).…”
Section: Formation Of Phosphatidylinositol 345-trisphosphate (Ptdinmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is not clear that this phosphorylation event can regulate SHIP1 activity (14). We have demonstrated that SHIP1 can be phosphorylated and activated by the cyclic AMPdependent protein kinase (PKA) both in vitro and in cells, highlighting a new mode of SHIP1 regulation (18).…”
Section: Formation Of Phosphatidylinositol 345-trisphosphate (Ptdinmentioning
confidence: 99%
“…Phosflow Fix Buffer I and Perm Buffer III were purchased from BD Biosciences. The sources of all other reagents have been published (18).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations